Antharjanam : memoirs of a Namboodiri woman - Nilayamgode, Devaki; Menon, Indira; Menon, Radhika; Devika, J. (New Delhi ; Oxford : Oxford University Press, 2012)
Autobiography of a leader of the women's right movement in Kerala, India.
Includes bibliographical references (p. xxxi).
Keywords: Nambudiris -- India -- Kerala -- Biography; Women -- India -- Kerala -- Biography